KEMAMPUAN MENULIS TEKS PERSUASI SISWA KELAS VIII SEMESTER II SMP N 2 KOTA SOLOK TAHUN PELAJARAN 2021/2022 - Yolla Febriani; Rini Wirasty B; Mega Putri (Program Studi Pendidikan Bahasa Indonesia, , Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mahaputra Muhammad Yamin, 2022)
This research is motivated by several factors: among others, students lack motivation to write, and students' low ability to think, and at least mastery of vocabulary make it difficult for students to develop ideas. Student learning outcomes have not reached the Minimum Completeness Criteria (KKM), which is 77. The purpose of this study is to describe the ability to write persuasive texts for class VIII in the second semester of SMP N 2 Solok City for the academic year 2021/2022. This research was conducted at SMP N 2 Solok City in class VIII semester II in May 2022. This type of research is quantitative research using descriptive method. Research data obtained through performance tests. The research data were analyzed based on the assessment indicators on the research instrument. Overall, the ability to write persuasive texts for grade VIII second semester students of SMP N 2 Solok City is described based on the structure and linguistic rules of persuasion texts. The ability to write persuasive texts based on the structure of persuasive texts is in good qualification with an average of 80,3. The ability to write persuasive texts based on the language rules of persuasive texts is in good qualification with an average of 85,86. Thus, it can be concluded that the ability to write persuasive texts for class VIII second semester students of SMP N 2 Solok City in the 2021/2022 academic year is 83.07 who are in good qualification.